Sosialisasi Empat Pilar Literasi Digital Sebagai Upaya Menumbuh Kembangkan Sikap Cinta Bangga Remaja terhadap Produk dan Budaya Tanah Air: - - Fitriyah, Neka; Isti Nursih (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this activity is to provide socialization and provide knowledge so that adolescents know and understand the four pillars of digital literacy, and so that adolescents can utilize the digital space as a means of fostering and developing an attitude of pride and love for the country's culture and products. Dialogical and interactive methods are used in this activity with the aim of making it easier for participants to understand the material given. This activity is carried out through five stages, namely: planning stage, pre-test; Socialization; simulation, and the post-test stage. The activity was attended by 75 students, with the results of the activity showing an increase in the breadth and comprehensiveness of adolescents' knowledge about the four pillars of digital literacy, culture, and products in the country. Participants become fully aware and aware of digital security, digital proficiency, digital ethics, digital culture, culture of the homeland and products of the homeland. The participants even learned how to avoid hoax news, cyberbullying, scheming and cybercrime.